TASMIM ALTADRIBAT ALLUGHAWIAT ALMUSTAFADAT MIN USLUB ALAMR FI KITAB ALHISN ALMUKHTAR MIN SAHIH ALADHKAR - Budiansyah; Rifa’iy Karsayuda; Rizal Firdaus; Rio Nandes (SHAWTUL ARAB, 2024)
Al-insyâ’ al-thalabiy is one of the rhetorical methods, and it is one of the chapters of the science of meanings. One of the methods of that section is the matter. The book Al-Hosn Al-Mukhtar from Sahih Al-Adhkaar includes this method, with different meanings according to the context of the hadith and the context. It is difficult to comprehend those intended meanings due to the inability of learners to understand them, especially in the science of rhetoric. This research aims to know the hadiths that include the style of the command and its meanings in the book Al-Hosn Al-Mukhtar from Sahih Al-Adhkar. And this research followed the descriptive analytical approach. The results of this research are developing the linguistic exercises learned from the imperative style in the book Al-Hisn Al-Mukhtar from Sahih Al-Azkar using the inductive method, which consists of observing examples of the style, then deducing the general rules for each style with the exercises